Moderating effect of ammonia on particle growth and stability of quasi-monodisperse silver nanoparticles synthesized by the Turkevich method - Gorup, Luiz F.; Longo, Elson [UNESP]; Leite, Edson R.; Camargo, Emerson R. (Elsevier, 2011)
A new method to stabilize silver nanoparticles by the addition of ammonia is proposed. Colloidal dispersions of silver nanoparticles were synthesized by the Turkevich method using sodium citrate to reduce silver nitrate at high pH and at 90 °C. After approximately 12 min, a diluted ammonia solution was added to the reaction flask to form soluble diamine silver (I) complexes that played an important growth moderating role, making it possible to stabilize metallic silver nanoparticles with sizes as small as 1.6 nm after 17 min of reaction. Colloidal dispersions were characterized by UV-visible absorption spectroscopy, X-ray diffraction, and transmission electronic microscopy.
Keywords: Silver nanoparticles; Turkevich method; Growth and stability